Practolol-induced autoantibodies and their relation to oculo-cutaneous complications. Issue 616 (February 1977) - Jachuck, S. J.; Stephenson, J.; Bird, T.; Jackson, F. S.; Clark, F.
Abstract : Tissue auto-antibodies were investigated in fifty-one patients (twenty-five female, twenty-six male) receiving practolol for ischaemic heart disease or dysrhythmias and compared with those found in 204 patients (fifty-eight female, 146 male) with ischaemic heart disease who did not receive practolol. Antinuclear factor (ANF) was found in 24% female and 16% male patients receiving practolol, but only in 5% of female and 4% of male patients who were not taking practolol. Thyroid cytoplasmic antibody (TCA) was detected in 16% female and 20% of male patients receiving practolol, compared to 10% of females and 6% of males in the control group. The incidence of ANF and TCA was significantly higher (P less than 0-05) in patients receiving practolol compared to the control group. The occurrence of gastric parietal cell antibody (PCA) and smooth muscle antibody (SMA) was not associated with practolol therapy (odds ratio of 2-4 and 1-9 respectively). The incidence of skin and eye complications was found to be 10% and the female to male ratio of this complication was 4 : 1. The correlation between autoantibody production and oculo-cutaneous complications could not be established in such a small group but three of the patients with the complications were found to have PCA, although PCA was found not to be associated with practolol therapy. Four of the five patients with the complications did not have circulating ANF.